PH-responsive mica-cerium-zinc filler and visual self-early-warning marine anti-corrosion and anti-fouling paint

By using mica @ zinc oxide filler and visual self-warning composite materials in marine anticorrosion coatings, the problem of easy degradation and failure of traditional coatings in harsh environments is solved, and efficient anti-corrosion, anti-fouling and self-warning functions are achieved, extending the long-term effect of the anti-corrosion, anti-fouling and self-warning functions. The service life of the coating.

CN119463557AActive Publication Date: 2025-02-18TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411800331.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-18
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Traditional marine anticorrosion coatings are prone to micro defects and small pores during the preparation process, and are prone to degradation and failure under the action of ultraviolet rays and high temperatures, making it difficult to maintain effective protection performance in various harsh environments.

Method used

Using mica @ zinc oxide filler and visualized self-warning marine anti-corrosion and anti-fouling coating composite material, the pH-responsive mica/cerium is prepared by combining cerium salt-modified mica, zinc salt, metal color developer and polycarboxyl polymer. Zinc filler and combine it with materials such as epoxy resin to form a coating with self-warning function.

Benefits of technology

It significantly improves the UV resistance and anti-fouling performance of the coating, realizes the self-warning function, slows down the expansion of the corrosion area of ​​the substrate, enhances the overall protection performance, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463557A_ABST
    Figure CN119463557A_ABST
Patent Text Reader

Abstract

The invention discloses a pH-responsive mica-cerium-zinc filler and a visual self-early-warning marine anti-corrosion and anti-fouling coating. The filler effectively induces charge separation through construction of a heterostructure, improves photocatalytic performance and photocathode protection capability, and enhances anti-ultraviolet performance and anti-fouling performance of the coating disclosed by the invention; besides, an indicator released by the filler due to pH change can generate a dark red metal chelate in a damaged area of the base material, so that expansion of the corrosion area of the base material is slowed down, the corrosion area of the coating can be visually observed, and a visual self-early-warning function is achieved; meanwhile, active oxygen released by the filler can inhibit bacterial colonies from being attached to the surface of the coating, damage of microorganisms to a polymer structure and deposition of a biological membrane are effectively avoided, and the overall protection performance of the coating is enhanced; the coating disclosed by the invention integrates anti-corrosion, anti-fouling and self-early-warning functions, and aims to provide a stable and durable protection effect in a harsh seawater environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of marine anti-corrosion materials, and in particular to a composite material, a coating and a preparation method for a marine anti-corrosion and anti-fouling coating. Background Art

[0002] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.

[0003] In order to effectively protect metals from or reduce corrosion in marine environments, surface coating technology is particularly important. However, traditional protective coatings often have some micro defects and small pores in the preparation process to reduce the integrity of the system. In addition, under the action of ultraviolet radiation, the breakage of polymer molecular chains will be aggravated, resulting in degradation and aging of materials and exposure of defects. In addition, higher temperatures will intensify the polymer segments and thermal motion in the coating, thereby generating more pores and defects, accelerating the deterioration and failure process of the coating. At the same time, in actual use, the attachment of microorganisms is more likely to cause complex corrosion problems, further weakening the protective performance of the coating. Therefore, under the combined action of a variety of harsh environmental conditions, the corrosive medium will accelerate the penetration of the coating through these defects, thereby causing local corrosion of the substrate. Over time, the area of ​​local corrosion of the substrate gradually expands, causing the coating to lose its protective ability before reaching its expected service life. Therefore, it is of great significance to develop intelligent protective coatings with corrosion warning functions, corrosion inhibition and repair functions, and anti-fouling adhesion capabilities, so that timely repairs can be carried out before the substrate suffers from severe corrosion, thereby extending the service life of the entire protective system.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may contain information that does not constitute prior art. Summary of the invention

[0005] In view of at least one of the above technical problems, the present disclosure provides mica@zinc oxide filler and a composite material for a visual self-warning marine anti-corrosion and anti-fouling coating to solve the problem that mica filler will produce uneven dispersion and agglomeration in the coating, thereby affecting the improvement of the anti-corrosion and anti-fouling performance of the coating.

[0006] In the first aspect, the pH-responsive mica@cerium-zinc filler comprises:

[0007] Cerium salt modified mica, zinc salt, metal developer and polycarboxyl polymer.

[0008] In the present disclosure and possible embodiments, the cerium salt is one or more of cerium chloride, cerium sulfate, cerium acetate, cerium perchlorate or cerium nitrate;

[0009] The mica is one or more of muscovite, biotite, sericite or conductive mica, and its specification is 200-800 mesh;

[0010] The zinc salt is one or more of zinc chloride, zinc sulfate, zinc acetate or zinc nitrate;

[0011] The metal developer is o-phenanthroline and / or 5,6-diamino-1,10-o-phenanthroline;

[0012] The polycarboxyl polymer is one or more of polyacrylic acid, polylactic acid, sodium polystyrene sulfonate or polyacrylamide-2-acrylamide-2-methylpropane sulfonic acid.

[0013] In a second aspect, a method for preparing the pH-responsive mica@cerium-zinc filler according to any one of the first aspects comprises:

[0014] Preparation of cerium salt modified mica;

[0015] After dissolving the metal color developer in a chlorine-containing solvent, a mixed aqueous solution of zinc salt and the cerium salt-modified mica is added, and after stirring evenly, a second alkali solution is added to form a mixed system. After the mixed system is reacted at a set temperature for a set time, a polycarboxyl polymer is added and the reaction is continued. The reaction product obtained is the pH-responsive mica@cerium-zinc filler.

[0016] In the present disclosure and possible embodiments, the method for preparing cerium salt-modified mica comprises:

[0017] A first base is added to an alcohol dispersion solution of mica and cerium salt to form a reaction system, the reaction system is reacted at 150-200° C. for 10-18 hours, and the reaction product is dried and calcined to obtain the cerium salt-modified mica.

[0018] In the present disclosure and possible embodiments, the alcohol-to-water ratio of the alcohol dispersion solution is 1:4 to 5:1, and the alcohol is ethanol;

[0019] The first base is NaOH, KOH or NH 4 One or more of OH;

[0020] By mass, mica powder: cerium salt: ethanol: water: first alkali = 0.8-5.0: 0.4-4.0: 10.0-100.0: 30.0-200.0: 0.4-5.0;

[0021] The calcination temperature is 500-800°C and the calcination time is 4-8h;

[0022] The drying temperature is 80-100° C., and the drying time is 12-48 hours.

[0023] In the present disclosure and possible embodiments, a cationic surfactant is also added to the mixed system;

[0024] The reaction time at the set temperature is to react at 30-50° C. for 1-3 hours, then raise the temperature to 50-65° C. and continue the reaction for 3-6 hours; the addition of the polycarboxyl polymer and continued reaction is to react at 60-75° C. for 1-4 hours.

[0025] In the present disclosure and possible embodiments, the chlorinated solvent is dichloromethane and / or chloroform;

[0026] The cationic surfactant is a mixture of one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate;

[0027] The second base is NaOH and / or KOH;

[0028] In parts by mass, cerium salt modified mica: metal color developer: chlorine-containing solvent: cationic surfactant: zinc salt: water: second base: polycarboxyl polymer = 1.0-10.0: 1.0-18.0: 10.0-100.0: 2.0-20.0: 0.2-3.0: 120.0-1000.0: 1.2-18.0: 0.1-2.0.

[0029] In a third aspect, the visual self-warning marine anti-corrosion and anti-fouling coating comprises:

[0030] The pH responsive mica@cerium zinc filler described in any one of the first aspects.

[0031] In the present disclosure and possible embodiments, the coating composition also includes:

[0032] Epoxy resins, solvents and curing agents;

[0033] The epoxy resin is E51 type and / or E44 type epoxy resin, and the curing agent is an amine curing agent;

[0034] The amine curing agent is phenolic amine and / or polyether amine;

[0035] The solvent is a mixed solvent of a benzene solvent and an alcohol solvent, and the mass ratio of the benzene solvent to the alcohol solvent is 3:1-1:5; the benzene solvent is toluene and / or xylene; and the alcohol solvent is n-butanol and / or amyl alcohol.

[0036] In the present disclosure and possible embodiments, by mass, epoxy resin: solvent: curing agent: pH responsive mica@cerium zinc filler = 1.5-15.0: 4.0-50.0: 1.2-15.0: 0.15-2.0.

[0037] The present disclosure has the following beneficial effects:

[0038] The pH-responsive mica / cerium zinc filler and the visual self-warning marine anticorrosion and antifouling coating disclosed in the present invention, wherein the SCC@ZPhP filler effectively induces charge separation by building a heterogeneous structure, thereby improving the photocatalytic performance and photocathode protection ability, thereby greatly enhancing the anti-ultraviolet performance and anti-fouling performance of the coating; in addition, the indicator released by the SCC@ZPhP filler due to pH changes can generate a deep red metal chelate in the damaged area of ​​the substrate, which not only slows down the expansion of the corrosion area of ​​the substrate, but also enables the corrosion area of ​​the coating to be visually observed, thereby realizing the self-warning function, which is actually It is extremely convenient in work and helps to take maintenance measures in time; at the same time, the active oxygen released by the SCC@CZPhP filler can inhibit the attachment of bacteria colonies on the surface of the coating, effectively avoiding the damage of microorganisms to the polymer structure and the deposition of biofilm, thereby enhancing the overall protective performance of the coating; in addition, after the surface modification of the SCC@CZPhP filler, the compatibility and dispersibility with the coating are significantly improved, thereby enhancing the interaction between the coating and the substrate; therefore, the composite coating prepared in the present invention integrates anti-corrosion, anti-fouling and self-warning functions, and is intended to provide stable and durable protection in harsh seawater environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The above and other objects, features and advantages of the present disclosure will become more apparent through the following description of the embodiments of the present disclosure with reference to the accompanying drawings, in which:

[0040] Figure 1 is the XRD pattern of SC, SCC and pH-responsive mica / cerium zinc composite material (SCC@ZPhP) in Example 1 of the present disclosure;

[0041] Figure 2 is the Phen release kinetics of the pH-responsive mica / cerium zinc composite material (SCC@ZPhP) of Example 1 of the present disclosure at different pH values;

[0042] Figure 3 Figure a1 is the UV-visible DRS spectra of SC, SCC and SCC@ZPhP in Example 3; Figures a2 and a3 are the VB spectrum and band structure of the SCC@ZPhP material and the corrosion potential diagram of steel in Example 3, respectively;

[0043] Figure 4 The pH-responsive mica / cerium-zinc composite material and different concentrations of Fe in Example 2 of the present disclosure 2+ Color change diagram after ion reaction;

[0044] Figure 5Figures a1-a3 in the figure are respectively the impedance comparisons of the EP coating, the SC coating, and the SCC@ZPhP coating in Example 3 of the present disclosure after ultraviolet irradiation at different times;

[0045] Figure 6 Figures a1-a3 are respectively schematic diagrams of visual self-warning salt spray test of EP coating, SC coating, and SCC@ZPhP coating in Example 4 of the present disclosure;

[0046] Figure 7 Figures a1, b1, and c1 are respectively SEM images of the scratched areas of the EP coating, SC coating, and SCC@ZPhP coating in Example 4 of the present disclosure; Figures a2, b2, and c2 are respectively EDS images of the scratched areas of the EP coating, SC coating, and SCC@ZPhP coating in Example 4 of the present disclosure;

[0047] Figure 8 Figures a\b\c\d are schematic diagrams of anti-fouling tests of the coating and epoxy coating of Example 2 of the present disclosure on different bacteria and seaweeds respectively. DETAILED DESCRIPTION

[0048] The present disclosure is described below based on embodiments, but it is worth noting that the present disclosure is not limited to these embodiments. In the detailed description of the present disclosure below, some specific details are described in detail. However, for the parts that are not described in detail, those skilled in the art can also fully understand the present disclosure.

[0049] In addition, those skilled in the art should understand that the drawings are only provided to illustrate the purpose, features and advantages of the present disclosure, and the drawings are not actually drawn to scale.

[0050] At the same time, unless the context clearly requires otherwise, the words "include", "comprises" and similar words throughout the specification and claims should be interpreted as inclusive rather than exclusive or exhaustive; that is, the meaning is "including but not limited to".

[0051] The following are preferred embodiments of the present disclosure.

[0052] Example 1

[0053] (1) Preparation of cerium salt modified mica SCC:

[0054] Calculated by mass, 0.8 parts of mica SC and 0.4 parts of Ce(NO) 3 6H 2O was dispersed in 40 mL of solution (alcohol-water ratio was 1:4) and stirred thoroughly for 1 h. Subsequently, 0.4 parts of NaOH was slowly added to the above solution and stirring was continued for 2 h. The mixture was then transferred to a Teflon stainless steel autoclave and reacted at 160 °C for 12 h. After cooling, the product was collected by centrifugation and dried in an oven at 80 °C for 12 h. Finally, the powder was transferred to a porcelain crucible and calcined at 500 °C for 8 h to obtain cerium salt-modified mica SCC.

[0055] (2) Preparation of pH-responsive mica / cerium zinc composite material SCC@ZPhP:

[0056] First, 1.0 part of o-phenanthroline Phen was added to a 150 mL three-necked flask containing 6.0 parts of chloroform and 4.0 parts of dichloromethane, and then 2.0 parts of sodium dodecyl sulfate SDS and 60 mL of deionized water were added to the above solution and mechanically stirred at 45 ° C for 2 h. Then, 1.8 parts of Zn(CH 3 COO 2 40 mL of deionized water with 1.0 part of SCC was added dropwise to the mixed solution, and 1.2 parts of NaOH was added after continuous stirring for 1.5 hours. After the mixed system was fully reacted at 30°C for 3 hours, the temperature was raised to 50°C and the reaction was continued for 6 hours. Subsequently, 0.1 part of polyacrylic acid PAA was added to the above mixed system and continued to stir at 60°C for 4 hours. After the reaction was completed, the mixed solution was washed with deionized water and the SCC@ZPhP particles were collected by centrifugation and then dried in an oven at 80°C for 12 hours.

[0057] (3) Preparation of visual self-warning marine anti-corrosion and anti-fouling coatings:

[0058] First, Q235 carbon steel was polished with 400-mesh and 1000-mesh sandpaper, respectively, and then cleaned with ethanol and dried in an oven. Then, 1.5 parts of EP and 1.2 parts of curing agent were added to 4.0 parts of solvent (xylene: 1-butanol = 3:1) to form a uniform dispersion under ultrasound. Then 0.15 parts of SCC@ZPhP were mixed with the above dispersion and ultrasound was applied for 20 minutes. Subsequently, the above mixture was sprayed on carbon steel at a pressure of 0.2 MPa and cured at 50°C and 80°C for 4 hours, respectively.

[0059] exist Figure 1 In the SCC curve, the peaks at 2θ=8.6°, 20.8°, 26.6°, 36.5° and 50.1° are the special diffraction peaks of SC. New diffraction peaks were observed at 2θ=28.6°, 33.0°, 47.4° and 56.2°, which are attributed to CeO 2 The (111), (200), (220) and (311) crystal planes of CeO 2The particles have been loaded on the surface of SC. Characteristic diffraction peaks of ZnO at 2θ = 31.7°, 34.3°, 36.2°, 62.7°, and 67.7° can be observed in the XRD pattern of the SCC@ZPhP composite, which further proves the loading of ZnO container and the synthesis of SCC / ZnO heterostructure.

[0060] Figure 2 The pH-responsive mica / zinc cerium composite material (SCC@ZPhP) of Example 1 of the present disclosure has a Phen release kinetics at different pH values. Figure 2 It can be seen that the release rate of Phen in neutral solution is the lowest, and the release rate is about 28.9% after immersion for 48 hours, indicating that SCC@ZPhP can effectively inhibit the leakage of Phen in a neutral environment. Under the condition of pH = 10, the release rate is significantly accelerated. After immersion for 24 hours, the release rate of Phen in SCC@ZPhP reaches 75.9%. With the extension of immersion time, the release amount of Phen gradually increases, and the release rate reaches 85.0% after 48 hours. Under acidic conditions, SCC@ZPhP also shows a higher release amount and faster release rate. After immersion for 48 hours, the release rate of Phen reaches 59.9%, which is twice the release amount under neutral conditions. The results show that the SCC@ZPhP material has pH responsiveness, which can prevent the premature leakage of Phen and is conducive to on-demand release during actual corrosion processes.

[0061] Example 2

[0062] (1) Preparation of cerium salt modified mica:

[0063] Calculated by mass, 4.0 parts of SC and 2.0 parts of Ce(NO) 3 6H 2 O was dispersed in 200 mL of solution and stirred thoroughly for 1 h (alcohol-water ratio was 5:1). Subsequently, 2.4 parts of NaOH were slowly added to the above solution and stirred for 2 h. The mixture was then transferred to a Teflon stainless steel autoclave and reacted at 160 °C for 12 h. After cooling, the product was collected by centrifugation and dried in an oven at 80 °C for 12 h. Finally, the powder was transferred to a porcelain crucible and calcined at 800 °C for 4 h to obtain cerium salt-modified mica SCC.

[0064] (2) Preparation of pH-responsive mica / cerium zinc composite material SCC@ZPhP:

[0065] First, 5.0 parts of Phen were added to a 500 mL three-necked flask containing 60 parts of chloroform and 40 parts of dichloromethane, and then 10 parts of SDS and 300 mL of deionized water were added to the above solution and mechanically stirred at 45 °C for 2 h. Then, 10.0 parts of Zn(CH 3 COO2 40 mL of deionized water with 5.0 parts of SCC was added dropwise to the mixed solution, and 8.0 parts of NaOH was added after continuous stirring for 1.5 hours. After the mixed system was fully reacted at 45°C for 1 hour, the temperature was raised to 65°C and the reaction was continued for 3 hours. Subsequently, 0.5 parts of PAA was added to the above mixed system and continued to stir at 65°C for 1 hour. After the reaction was completed, the mixed solution was washed with deionized water and the SCC@ZPhP particles were collected by centrifugation and then dried in an oven at 80°C for 12 hours.

[0066] (3) Preparation of visual self-warning marine anti-corrosion and anti-fouling coatings:

[0067] First, Q235 carbon steel was polished with 400-mesh and 1000-mesh sandpaper, respectively, and then cleaned with ethanol and dried in an oven. Then, 9.0 parts of EP and 7.2 parts of curing agent were added to 20.0 parts of solvent (xylene: 1-butanol = 1:5) to form a uniform dispersion under ultrasound. Then 0.75 parts of SCC@ZPhP were mixed with the above dispersion and ultrasound was applied for 20 minutes. Subsequently, the above mixture was sprayed on carbon steel at a pressure of 0.2 MPa, and after curing at 60°C for 6 hours, it was continued to cure at 100°C for 2 hours.

[0068] Figure 4 The pH-responsive mica / cerium-zinc composite material and different concentrations of Fe in Example 2 of the present disclosure 2+ Color change diagram after ion reaction. The initial color of the solution is milky white. 2+ With the gradual increase of concentration, the color of the mixed solution changes from light yellow to orange to dark red, indicating that [Fe(Phen) 2 ] 2+ Formation of ligand compounds; even in the presence of low concentrations of Fe 2+ ions, the SCC@ZPhP solution will also show an obvious color change.

[0069] Figure 8 It is a schematic diagram of the antifouling test of the coating of Example 2 of the present disclosure and the epoxy EP coating for different bacteria (CG: blank control group), wherein a\b are for bacteria, and c\d are for seaweed. It can be seen from Figures ad that the epoxy EP coating containing bacteria (Escherichia coli, Staphylococcus aureus) and seaweed is placed in a light / dark environment for antifouling performance testing. After cultivation, it can be found that the antifouling effect of the EP coating is extremely poor, and a large number of colonies survive on the culture medium and the coating surface. On the contrary, after the SCC / ZPhP coating is cultivated in a light / dark environment, it can be seen that the number of colonies and seaweed inside the culture medium is significantly reduced, showing an excellent antifouling effect.

[0070] Example 3

[0071] (1) Preparation of cerium salt modified mica:

[0072] Calculated by mass, 2.4 parts of SC and 1.5 parts of Ce(NO) 3 6H 2 O was dispersed in 150 mL of solution and stirred thoroughly for 1 h (alcohol-water ratio was 1:4). Subsequently, 1.4 parts of NaOH were slowly added to the above solution and stirred for 2 h. The mixture was then transferred to a Teflon stainless steel autoclave and reacted at 160 °C for 12 h. After cooling, the product was collected by centrifugation and dried in an oven at 80 °C for 12 h. Finally, the powder was transferred to a porcelain crucible and calcined at 650 °C for 7 h to obtain cerium salt-modified mica SCC.

[0073] (2) Preparation of pH-responsive mica / cerium zinc heterogeneous composite material SCC@ZPhP:

[0074] First, 4.0 parts of Phen were added to a 500 mL three-necked flask containing 18.0 parts of chloroform and 12.0 parts of dichloromethane, and then 6 parts of SDS and 60 mL of deionized water were added to the above solution and mechanically stirred at 45 °C for 2 h. Then, 7.0 parts of Zn(CH 3 COO 2 60 mL of deionized water and 3.3 parts of SCC were added dropwise to the mixed solution, and 5.0 parts of NaOH were added after continuous stirring for 1.5 hours. After the mixed system was fully reacted at 45°C for 1 hour, the temperature was raised to 65°C and the reaction was continued for 3 hours. Subsequently, 0.3 parts of PAA were added to the above mixed system and stirred at 65°C for another 1 hour. After the reaction was completed, the mixed solution was washed with deionized water and the SCC@ZPhP particles were collected by centrifugation and then dried in an oven at 80°C for 12 hours.

[0075] (3) Preparation of visual self-warning marine anti-corrosion and anti-fouling coatings:

[0076] First, Q235 carbon steel was polished with 400-mesh and 1000-mesh sandpaper, respectively, and then cleaned with ethanol and dried in an oven. Then, 3.0 parts of EP and 4.2 parts of curing agent were added to 7.0 parts of solvent (xylene: 1-butanol = 5:2) to form a uniform dispersion under ultrasound. Then 0.42 parts of SCC@ZPhP were mixed with the above dispersion and ultrasound was applied for 20 minutes. Subsequently, the above mixture was sprayed on carbon steel at a pressure of 0.2 MPa and cured at 60°C and 80°C for 6 hours.

[0077] Table 1 shows the Eg values ​​of SC / ZPhP and SCC / ZPhP in Example 3:

[0078] Table 1 Eg values ​​of SC / ZPhP and SCC / ZPhP

[0079]

[0080] Figure 3 is the UV-Vis DRS spectra (a1) of SC, SCC and SCC@ZPhP in Example 3 and V B Spectrum (a2), band structure and corrosion potential diagram of steel (a3). It can be seen from a1-a3 that SC has a low absorption capacity in the ultraviolet region due to its strong extinction shielding effect. SC / ZPhP only shows good absorption capacity in the ultraviolet region, allowing electron transitions, and cannot fully improve the light utilization efficiency of the system. In contrast, SC / ZPhP and CeO 2 The formed heterostructure has stronger absorption capacity for UVA and UVB. At the same time, the red shift of the absorption band improves the light absorption range of SCC@ZPhP and enhances the light capture ability of the material in a wider band.

[0081] At the same time, - / h + The effective spatial separation and narrower Eg make SCC@ZPhP more active in the UV / visible region (Table 1), which is beneficial to produce more e - / h + , thereby improving the light utilization and conversion performance of the system.

[0082] Depend on Figure 5 As shown in a1-a3 in the figure, due to the existence of internal defects in the EP coating, the poor compatibility of mica powder (SC) with the resin, and the lack of functional corrosion inhibition performance, a large number of corrosion products are produced on the substrate surface after long-term UV exposure. On the contrary, the surface of the visual self-warning marine anti-corrosion and anti-fouling coating (SCC@ZPhP) is intact after long-term light exposure, without obvious pitting and corrosion, and the impedance value of the coating can still reach 10 11 Ω·cm 2 , indicating that the overall anti-corrosion performance of the coating has been significantly improved.

[0083] Example 4

[0084] (1) Preparation of cerium salt modified mica:

[0085] Calculated by mass, 5.0 parts of SC and 4.0 parts of Ce(NO) 3 6H 2O was dispersed in 300 mL of solution and stirred thoroughly for 1 h (alcohol-water ratio was 1:4). Subsequently, 5.0 parts of NaOH were slowly added to the above solution and stirred for 2 h. The mixture was then transferred to a Teflon stainless steel autoclave and reacted at 160 °C for 12 h. After cooling, the product was collected by centrifugation and dried in an oven at 80 °C for 12 h. Finally, the powder was transferred to a porcelain crucible and calcined at 550 °C for 7 h to obtain cerium salt-modified mica SCC.

[0086] (2) Preparation of pH-responsive mica / cerium zinc heterogeneous composite material SCC@ZPhP:

[0087] First, 18 parts of Phen were added to a 500 mL three-necked flask containing 60.0 parts of chloroform and 40.0 parts of dichloromethane, and then 30.0 parts of SDS and 100 mL of deionized water were added to the above solution and mechanically stirred at 45 °C for 2 h. Then, 20.0 parts of Zn(CH 3 COO 2 100 mL of deionized water with 10.0 parts of SCC was added dropwise to the mixed solution, and 18.0 parts of NaOH was added after continuous stirring for 1.5 hours. After the mixed system was fully reacted at 45°C for 1 hour, the temperature was raised to 65°C and the reaction was continued for 3 hours. Subsequently, 2.0 parts of PAA were added to the above mixed system and continued to stir at 65°C for 1 hour. After the reaction, the mixed solution was washed with deionized water and the SCC@ZPhP particles were collected by centrifugation and then dried in an oven at 80°C for 12 hours.

[0088] (3) Preparation of visual self-warning marine anti-corrosion and anti-fouling coatings:

[0089] First, Q235 carbon steel was polished with 400-mesh and 1000-mesh sandpaper, respectively, and then cleaned with ethanol and dried in an oven. Then, 15.0 parts of EP and 15.0 parts of curing agent were added to 50.0 parts of solvent (xylene: 1-butanol = 1:4) to form a uniform dispersion under ultrasound. Then 2.0 parts of SCC@ZPhP were mixed with the above dispersion and ultrasonicated for 20 minutes. Subsequently, the above mixture was sprayed on carbon steel at a pressure of 0.2 MPa and cured at 60°C and 90°C for 8 hours.

[0090] Depend on Figure 6As shown in a1-a3, after long-term exposure to salt spray environment, EP and SC accumulate a large amount of corrosion products in the scratch area of ​​the two coatings due to the lack of functional protection, and obvious pitting occurs in the undamaged area. In contrast, the corrosion products of SCC@ZPhP are relatively few, and there is no obvious diffusion area. In addition, the dark red mark formed around the scratch area of ​​the coating indicates that the indicator is released, and the composite deposition protective film formed further slows down the erosion of the corrosive medium. At the same time, the interaction between SCC@ZPhP and the substrate not only improves the shielding and barrier properties of the coating, but also reduces the generation of internal defects in the system, so that the coating still has excellent stability and long-term corrosion resistance. The generation of dark red marks provides an intuitive early warning function for local corrosion of the substrate, which is conducive to timely discovery of potential locations of substrate damage and maintenance.

[0091] from Figure 7 From a1-a2 in the figure, it can be seen that a large number of loose corrosion products containing Fe and O elements are scattered in the EP scratch area, indicating that the substrate has been severely corroded. For SC, many corrosion products are also formed in the matrix scratch area (b1-b2). In contrast, a relatively dense shielding film is produced in the SCC@ZPhP scratch area to inhibit the penetration of the corrosive medium (c1). At the same time, the appearance of C, O, N, Ce and Zn elements in the SCC@ZPhP scratch area further indicates the release of phen and the formation of a protective film containing Ce / Zn (c2).

[0092] The above-described embodiments are only embodiments of the present disclosure, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the present disclosure. It should be noted that, for a person of ordinary skill in the art, without departing from the concept of the present disclosure, several variations, equivalent substitutions, improvements, etc. may be made, all of which fall within the scope of protection of the present disclosure. Therefore, the scope of protection of the present disclosure shall be subject to the attached claims.

Claims

1. A pH-responsive mica@cerium-zinc filler, characterized in that: Its composition includes: Cerium salt modified mica, zinc salt, metal developer and polycarboxyl polymer.

2. The pH responsive mica@cerium zinc filler according to claim 1, characterized in that: The cerium salt is one or more of cerium chloride, cerium sulfate, cerium acetate, cerium perchlorate or cerium nitrate; The mica is one or more of muscovite, biotite, sericite or conductive mica, and its specification is 200-800 mesh; The zinc salt is one or more of zinc chloride, zinc sulfate, zinc acetate or zinc nitrate; The metal developer is o-phenanthroline and / or 5,6-diamino-1,10-o-phenanthroline; The polycarboxyl polymer is one or more of polyacrylic acid, polylactic acid, sodium polystyrene sulfonate or polyacrylamide-2-acrylamide-2-methylpropane sulfonic acid.

3. The method for preparing the pH-responsive mica@cerium-zinc filler according to claim 1 or 2, characterized in that: include: Preparation of cerium salt modified mica; After the metal developer is dissolved in a chlorine-containing solvent, zinc salt and the cerium salt modified cloud are added. The mixed aqueous solution of the mother is stirred evenly and then a second alkali solution is added to form a mixed system. After the mixed system is reacted at a set temperature for a set time, a polycarboxyl polymer is added and the reaction is continued. The reaction product obtained is the pH responsive mica@cerium zinc filler.

4. The method for preparing the pH-responsive mica@cerium-zinc filler according to claim 3, characterized in that: The method for preparing cerium salt modified mica comprises: The first base is added to the alcohol dispersion solution of mica and cerium salt to form a reaction system. The reaction system is reacted at 150-200° C. for 10-18 hours, and the reaction product is dried and calcined to obtain the cerium salt modified mica.

5. The preparation method of the pH-responsive mica@cerium-zinc filler according to claim 4, Features: The alcohol-water ratio of the alcohol dispersion solution is 1:4-5:1, and the alcohol is ethanol; The first base is one or more of NaOH, KOH or NH4OH; By mass, mica powder: cerium salt: ethanol: water: first alkali = 0.8~5.0: 0.4~4.0: 10.0~100.0: 30.0~200.0: 0.4~5.0; The calcination temperature is 500-800 °C and the calcination time is 4-8 h. The drying temperature is 80-100°C, and the drying time is 12-48 hours.

6. The preparation method of the pH-responsive mica@cerium-zinc filler according to claim 5, Features: A cationic surfactant is also added to the mixed system; The set reaction time at the set temperature is to react at 30-50°C for 1-3 hours, then raise the temperature to 50-65°C and continue the reaction for 3-6 hours; the adding of the polycarboxyl polymer and continuing the reaction is to react at 60-75°C for 1-4 hours.

7. The preparation method of the pH-responsive mica@cerium-zinc filler according to claim 6, Features: The chlorinated solvent is dichloromethane and / or chloroform; The cationic surfactant is sodium lauryl sulfate, sodium lauryl sulfonate or A mixture of one or more of sodium dodecylbenzene sulfonate; The second base is NaOH and / or KOH; By mass, cerium salt modified mica: metal color developer: chlorinated solvent: cationic surface Surfactant: zinc salt: water: second base: polycarboxyl polymer = 1.0 ~ 10.0: 1.0 ~ 18.0: 10.0 ~ 100.0: 2.0 ~ 20.0: 0.2 ~ 3.0: 120.0 ~ 1000.0: 1.2 ~ 18.0: 0.1 ~2.

0.

8. A visual self-warning marine anti-corrosion and anti-fouling coating, characterized in that: Its composition include: The pH responsive mica@cerium zinc filler according to claim 1 or 2.

9. The visual self-warning marine anti-corrosion and anti-fouling coating according to claim 8 is characterized in that: The composition also includes: Epoxy resins, solvents and curing agents; The epoxy resin is E51 type and / or E44 type epoxy resin, and the curing agent is an amine curing agent; The amine curing agent is phenolic amine and / or polyether amine; The solvent is a mixed solvent of a benzene solvent and an alcohol solvent, and the mass ratio of the benzene solvent to the alcohol solvent is 3:1-1:5; the benzene solvent is toluene and / or xylene; and the alcohol solvent is n-butanol and / or amyl alcohol.

10. The visual self-warning marine anti-corrosion and anti-fouling coating according to claim 9 is characterized in that: By mass, epoxy resin: solvent: curing agent: pH responsive mica @ cerium zinc filler = 1.5 ~ 15.0: 4.0 ~ 50.0: 1.2 ~ 15.0: 0.15 ~ 2.0.

Citation Information

Patent Citations

  • Mica / zinc oxide and composite material and paint for marine anti-corrosion and anti-fouling coating

    CN116836578A

  • Surface-modified inorganic filler for heavy-duty anticorrosion paint and method for manufacturing same

    KR1020140049238A